Sex and gender differences in Alzheimer's disease: current challenges and implications for clinical practice: Position paper of the Dementia and Cognitive Disorders Panel of the European Academy of Neurology. (3rd April 2020) - Ferretti, M. T.; Martinkova, J.; Biskup, E.; Benke, T.; Gialdini, G.; Nedelska, Z.; Rauen, K.; Mantua, V.; Religa, D.; Hort, J.; Santuccione Chadha, A.; Schmidt, R.
Abstract : Alzheimer's disease (AD) is characterized by high heterogeneity in disease manifestation, progression and risk factors. High phenotypic variability is currently regarded as one of the largest hurdles in early diagnosis and in the design of clinical trials; there is therefore great interest in identifying factors driving variability that can be used for patient stratification. In addition to genetic and lifestyle factors, the individual's sex and gender are emerging as crucial drivers of phenotypic variability. Evidence exists on sex and gender differences in the rate of cognitive deterioration and brain atrophy, and in the effect of risk factors as well as in the patterns of diagnostic biomarkers. Such evidence might be of high relevance and requires attention in clinical practice and clinical trials. However, sex and gender differences are currently seldom appreciated; importantly, consideration of sex and gender differences is not currently a focus in the design and analysis of clinical trials for AD. The objective of this position paper is (i) to provide an overview of known sex and gender differences that might have implications for clinical practice, (ii) to identify the most important knowledge gaps in the field (with a special regard to clinical trials) and (iii) to provide conclusions for future studies. This scientific statement is endorsed by the European Academy of Neurology.